Assessment of Beach Sand Quality of Samandag Beaches, Hatay, Turkey - Goksel Ozdilek, Hasan (Asian Journal of Chemistry, 2010)
This study provides information about trace metal levels along the southem (Samandag) beaches of Hatay Province, which is the southernmost province in Turkey. The Samandag Beaches consist of three beaches: Cevlik, Seyhhizir and Meydan from north to south. Among these beaches, Seyhhizir Beach is densely nested location by green sea turtles during the summer months. The object of this research is to reveal trace metal levels on the beaches. The results obtained from the analysis of trace metals, namely cadmium, copper, lead, zinc, indicated there are somewhat high trace metal concentrations in specific stations close to where raw sewage of Samandag dwellings is discharged by tanker trucks.